Effectiveness of Prefabricated Lumbar Sacral Orthosis (LSO) Corset for Pain Relief in Low Back Pain (LBP) Health Students - Rohmah, Salsabila Laili Nur; Utami, Feryanda; Karma, Agusni (Poltekkes Kemenkes Jakarta I, 2024)
Background: Low back pain (LBP) is a common musculoskeletal disorder often resulting from poor ergonomics. Students are particularly susceptible to LBP due to prolonged static positions and awkward postures. Objective: This study aims to evaluate the effectiveness of a prefabricated lumbar sacral orthosis (LSO) corset in reducing pain intensity and improving functional activity levels among students with LBP in the Dental Health and Prosthetics Orthotics Departments, Poltekkes Kemenkes Jakarta I. Method: A quantitative, pre-experimental one-group pre-test post-test design was employed, involving students from Poltekkes Kemenkes Jakarta I. Results: Among 30 students with LBP, 26 participants (86.7%) experienced a reduction in pain, while 4 (13.3%) continued to report moderate pain. Conclusion: The use of the prefabricated LSO corset significantly reduced pain levels and improved functional activity in affected Dental Health and Orthotics Prosthetics students at Jakarta Polytechnic I in 2024. Suggestions: Future studies should consider a larger participant pool, enhanced research monitoring, and comparisons between corsets with and without support bars for more robust findings.